Decline in ACEI/ARB Prescribing as Heart Failure Core Metrics Improve During Computer-Based Clinical Decision Support. (July 2014) - Caraballo, Pedro J.; Naessens, James M.; Klarich, Mark J.; Leutink, Dorinda J.; Peterson, James A.; Wagie, Amy E.; Manning, Dennis M.; Qian, Qi
Computer-based clinical decision-support systems are effective interventions to improve compliance with guidelines and quality measures. However, understanding of their long-term impact, including unintended consequences, is limited. The authors assessed the clinical impact of the sequential implementation of 2 such systems to improve the use of angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (ACEIs/ARBs) in inpatients with heart failure. Compliance with the core measure improved from 91.0% at baseline to 93.6% with the Pharmacy Care (P-Care) Rule and to 96.4% with the Centricity-Blaze (CE-Blaze) Rule. At the same time, prescriptions for ACEIs/ARBs documented in the hospital discharge summary decreased from 83.2% at baseline to 75.8% with the P-Care rule and to 64.1% with the CE-Blaze Rule. The inpatient mortality rate and the 30-day readmission rate did not change significantly. Better documentation of contraindications in the electronic medical record seems to account for the core measure improvement, even as ACEI/ARB therapy has unexpectedly declined.